ANALISIS PERBEDAAN REAKSI PASAR SAHAM SEBELUM DAN SESUDAH PENGUMUMAN KENAIKAN HARGA BBM DI BURSA EFEK INDONESIA - Chesa, Eristo; Prasetyo, Andrian Budi (Diponegoro Journal of Accounting, 2024)
Many important factors or events can affect the capital market, a phenomenon that can have an impact on capital market activities is the announcement of a price increase in the price of fuel oil (BBM) in Indonesia. Indonesia officially announced the increase in fuel oil prices through President Joko Widodo on September 3, 2022.The purpose of the following research is to find the capital market response by conducting research on the difference in abnormal returns as well as trading volume before and after the fuel price increase on September 3, 2022. The following research applies an event study approach, the sample used in this research is 37 firms. The results of the following research prove that the capital market did not react significantly to the announcement of the fuel price increase on September 3, 2022. Based on the results of testing the difference in the average abnormal return of the period before and after the announcement there is no significant difference. different, on the other hand, the results of testing the difference in the average trading volume (ATV) did not show a significant difference between the time before and after the announcement of the fuel price increase on September 3, 2022.